Moderate elevation of intracellular creatine by targeting the creatine transporter protects mice from acute myocardial infarction. - Lygate, C; Bohl, S; ten Hove, M; Faller, K; Ostrowski, P; Zervou, S; Medway, D; Aksentijevic, D; Sebag-Montefiore, L; Wallis, J; Clarke, K; Watkins, H; et al. (2012)
AIMS: Increasing energy storage capacity by elevating creatine and phosphocreatine (PCr) levels to increase ATP availability is an attractive concept for protecting against ischaemia and heart failure. However, testing this hypothesis has not been possible since oral creatine supplementation is ineffectual at elevating myocardial creatine levels. We therefore used mice overexpressing creatine transporter in the heart (CrT-OE) to test for the first time whether elevated creatine is beneficial in clinically relevant disease models of heart failure and ischaemia/reperfusion (I/R) injury. METHODS AND RESULTS: CrT-OE mice were selected for left ventricular (LV) creatine 20-100% above wild-type values and subjected to acute and chronic coronary artery ligation. Increasing myocardial creatine up to 100% was not detrimental even in ageing CrT-OE. In chronic heart failure, creatine elevation was neither beneficial nor detrimental, with no effect on survival, LV remodelling or dysfunction. However, CrT-OE hearts were protected against I/R injury in vivo in a dose-dependent manner (average 27% less myocardial necrosis) and exhibited greatly improved functional recovery following ex vivo I/R (59% of baseline vs. 29%). Mechanisms contributing to ischaemic protection in CrT-OE hearts include elevated PCr and glycogen levels and improved energy reserve. Furthermore, creatine loading in HL-1 cells did not alter antioxidant defences, but delayed mitochondrial permeability transition pore opening in response to oxidative stress, suggesting an additional mechanism to prevent reperfusion injury. CONCLUSION: Elevation of myocardial creatine by 20-100% reduced myocardial stunning and I/R injury via pleiotropic mechanisms, suggesting CrT activation as a novel, potentially translatable target for cardiac protection from ischaemia.